Effects of Self-Instruction and Time Management Techniques in Group Counseling to Reduce Academic Procrastination - Asri, Dahlia Novarianing; Kadafi, Asroful (Jurnal Kajian Bimbingan dan Konseling, 2020)
This study aims to discover the effectiveness of group counseling with self-instruction and time management techniques in decreasing academic procrastination in mathematics learning. This research used a randomized pre-test post-test comparison group design with sixteen participants selected through a purposive random sampling technique. Eight of those participants (group 1) used the self-instruction technique; meanwhile, the other eight participants (groups 2) used the time management technique. The data was obtained through an academic procrastination scale, referring to academic procrastination aspects, developed by Tuckman. Additionally, the Wilcoxon Signed Rank Test was used to test the effectiveness of both techniques, and the Mann-Whitney test was used to compare the efficacy of both techniques. The results indicate that group counseling with self-instruction and time management techniques are sufficient to lower the academic procrastination in mathematics learning. Further, the self-instruction group counseling is more effective to downturn academic procrastination than time management technique.